Czynniki ryzyka rozwoju Zespołu Stresu Pourazowego u żołnierzy uczestniczących w misjach wojskowych - Groth, Jarosław; Waszyńska, Katarzyna; Zyszczyk, Barbara (Wydawnictwo Naukowe UAM, 2013)
The present research aimed at answering the question of effects of the chosen factors of pretraumatic, traumatic and posttraumatic period on the prevalence of the posttraumatic stress disorder in a sample of soldiers participating in military missions in Iraq and Afghanistan (N = 50). The research was conducted in a military unit of British Armed Forces in London. The outcomes of PCL-M questionnaire indicated PTSD in 56% of the subjects (N = 28). According to the analysis, the percentage of correct classification of the model taking into account the variables of trauma intensity (chi2(1) = 37.1; p < 0.01), prior traumatization (chi2(1) = 24.8; p < 0.01) and the size of the group of individuals to provide support (chi2(1) = 0.9) is estimated to be 90%. The variables with the greatest impact on the development of PTSD proved to be the intensity of the trauma and early traumatization. The size of the group of people who can provide support proved to contribute to the occurrence of PTSD in combination with the other two variables.
Risk factors for the development of the posttraumatic stress disorder in soldiers participating in tours of duty
Keywords: combat stress; military mission; PTSD; trauma intensity; prior traumatization; support group